Biejiajian Pill Promotes the Infiltration of CD8+ T Cells in Hepatocellular Carcinoma by Regulating the Expression of CCL5 - Yang, Xuemei; Sun, Jialing; Wen, Bin; Wang, Yu; Zhang, Mingjia; Chen, Weicong; Zhao, Wenting; He, Chunyu; Zhong, Xiaodan; Liu, Yang; Li, Tong; Sun, Haitao; et al. (Frontiers in Pharmacology, 2021)
Tumor-infiltrating CD8+T lymphocytes are mostly associated with a favorable prognosis in numerous cancers, including hepatocellular carcinoma (HCC). Biejiajian Pill (BJJP) is a common type of traditional Chinese medicine that is widely used in the treatment of HCC in China. Previous studies showed that BJJP suppressed the growth of HCC cells both in vivo and in vitro, by exerting direct cytotoxic effects on tumor cells. The present study demonstrated that in addition to direct cytotoxicity, BJJP inhibits the growth of tumor cells by promoting the infiltration of CD8+T cells into the tumor in H22-bearing mice. Mechanistically, chemokine ligand 5 (CCL5) was identified as one of the most highly expressed chemokines by tumor cells in vivo after treatment with BJJP. Additionally, CCL5 was knocked down in H22 cells and the results showed that knockdown of the gene significantly impaired the infiltration of CD8+T cells in vivo. Furthermore, the effects of BJJP on human HCC cell lines were assessed in vitro. Similarly, cells treated with BJJP had higher expression of CCL5 mRNA, which was consistent with increased levels of CCL5 protein in human tumor cells. These findings provide new insights into the anticancer effects of BJJP, which regulated the expression of CCL5 and the infiltration of CD8+T cells. The results, therefore, suggest that BJJP has great potential application in clinical practice.